Free jazz: A concept poem - Windleburn, Maurice (Jazz Research Journal, 2022)
This concept poem ekphrastically manifests Ornette Coleman’s landmark album Free Jazz: A Collective Improvisation. Separated into two columns, the piece features the work of two quartets of poets, reflecting Coleman’s own separation of his double quartet ensemble into left and right recording channels. The poets Bob Kaufman, Jayne Cortez, Cecil Taylor and Lawrence Ferlinghetti are the quartet in the left column; Amiri Baraka, Langston Hughes, M. NourbeSe Philip and Boris Vian are the quartet in the right. The work of these poets has been scrambled and interwoven in the first and third-from-last stanzas, mimicking the two polymelodic interludes found in Coleman’s album. The remaining stanzas either combine lines from a quartet of poets or are entirely from the work of a single poet, who ‘solos’ against the quartet in the adjacent column (again, mimicking the general structure of Coleman’s album).